2008
DOI: 10.1007/s10571-008-9294-x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Plasminogen Activator Enhances the Hypoxia/reoxygenation-induced Impairment of the Blood–brain Barrier in a Primary Culture of Rat Brain Endothelial Cells

Abstract: Hemorrhagic transformation is a major complication associated with tissue plasminogen activator (tPA) therapy for ischemic stroke. We studied the effect of tPA on the blood-brain barrier (BBB) function with our in vitro monolayer model generated using rat brain microvascular endothelial cells subjected either to normoxia or to hypoxia/reoxygenation (H/R) with or without the administration of tPA. The barrier function was evaluated by the transendothelial electrical resistance (TEER), the permeability of sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…It has been documented that t-PA promotes MMP-9 secretion, NF-B activation, apoptosis, and barrier dysfunctions in H/R-stimulated ECs. 4,19 These results indicated that rt-PA facilitates cytokine-induced ROS generation ( Figure 6) and H/R-induced VCAM-1 induction in ECs ( Figure 4); thus, it is thought that rt-PA directly enhances proinflammatory signaling in ECs in the tMCAo mice. We believe that rt-PA is capable of accelerating cerebral infarction through proinflammatory responses independently of blood flow recovery when the ischemic region is highly restricted; however, reasons why rt-PA worsened cerebral infarction in the mice are currently obscure.…”
Section: Discussionmentioning
confidence: 86%
“…It has been documented that t-PA promotes MMP-9 secretion, NF-B activation, apoptosis, and barrier dysfunctions in H/R-stimulated ECs. 4,19 These results indicated that rt-PA facilitates cytokine-induced ROS generation ( Figure 6) and H/R-induced VCAM-1 induction in ECs ( Figure 4); thus, it is thought that rt-PA directly enhances proinflammatory signaling in ECs in the tMCAo mice. We believe that rt-PA is capable of accelerating cerebral infarction through proinflammatory responses independently of blood flow recovery when the ischemic region is highly restricted; however, reasons why rt-PA worsened cerebral infarction in the mice are currently obscure.…”
Section: Discussionmentioning
confidence: 86%
“…Commercially available endothelial cells (bEnd.3, ATCC, Manassas, VA) derived from the cerebral cortex of mice were used for oxygen glucose deprivation (OGD) studies as previously reported (Hiu et al, 2008). Cells were grown in high-glucose Dulbecco’s Modified Eagle Medium (DMEM; Invitrogen) in the presence of 10% fetal bovine serum (ATCC) and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…Hypoxia conditions consisted of 2 h hypoxia in a standard hypoxia chamber set to 0.1% oxygen, with or without the administration of 20 μM progesterone. Reoxygenation was initiated by adding serum-free, normoxic media (Hiu et al, 2008). TIB-186/IC21 cells were graciously donated by Robert Taylor, Emory University, and cultured in RPMI (Gibco, Grand Island, NY) containing 15% fetal bovine serum (ATCC) and penicillin/streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The flux of sodium fluorescein (Na-F) and Evans' bluealbumin across the endothelial monolayer was determined as previously described (Honda et al 2006;Nakagawa et al 2007;Hiu et al 2008). Cell culture inserts were transferred to 24-well plates containing 0.7-ml assay buffer (136-mM NaCl, 0.9-mM CaCl 2 , 0.5-mM MgCl 2 , 2.7-mM KCl, 1.5-mM KH 2 PO 4 , 10-mM NaH 2 PO 4 , 25-mM glucose, and 10-mM Hepes, pH 7.4) in the basolateral or lower compartments.…”
Section: Transendothelial Permeabilitymentioning
confidence: 99%